Silencio positivo, revisión de actos y cosa juzgada - Eva Desdentado Daroca (Revista Vasca de Administración Pública)
This article approaches the difficulties that arise when the judges establish that the absence of reply by the Administration has to be understood as an implied concession of what the citizen applied for, when the applicant did not really fulfil the requirements to obtain what he had asked for. In such a case the implied administrative act (concession) is illegal, but the question that arises is whether the Administration can still use the actions against the illegal act and obtain its annulment or this annulment can not be possible as a consequence of the res iudicata effect.